Simulation of a Regular Sampled Pulsewidth Modulation (PWM) Technique for a Multilevel Inverter - Mohd. Shafie, Bakar; Naziha, Ahmad Azli (IEEE, 2003)
Simulation of a multilevel inverter for high power applications employing a PWM unipolar symmetrical regular sampled technique based on a single carrier multilevel modulation strategy is presented in this paper. The equations related to this technique are used to design the gate signal generator blocks using Matlab Simulink. These blocks generate the gate signals for each of the multilevel inverter power devices and can later be compiled and downloaded to a dSPACE DSP controller board for real time digital implementation. The gate signal generator blocks are tested for various values of modulation index. The results of the simulation study are shown in the form of the PWM waveforms of the multilevel inverter modules as well as the gate signals for its power devices for comparison purposes.